Meningkatkan Mutu Lulusan dengan Memaksimal Fungsi Manajemen Pendidikan di Sekolah - Mochamad Fauzi Ali; Lilis Kholisah Nuryani (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2023)
Efforts to improve the quality of education by implementing educational management and establishing quality standards have been made by the government. However, to create a quality education, good governance is needed to support the achievement of educational goals, requiring effective educational management. This research aims to describe the educational management applied by RA Generasi Rabbani Ciamis to improve the quality of its graduates. The researcher interviewed the school principal, vice-principal, and a teacher, and analyzed various documents such as lesson plans, student reports, school programs, and facilities. The results show that the school has implemented effective educational management functions to improve the quality of its graduates, including planning, implementation, monitoring, evaluation, and improvement (PDCA). RA Generasi Rabbani Ciamis is aware of the importance of implementing educational management to produce quality students who are competitive upon graduation.